2022
DOI: 10.3390/su14031068
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Quality Indicators of Pressed Biofuel Produced from Coarse Herbaceous Plants and Determination of the Influence of Moisture on the Properties of Pellets

Abstract: Three coarse herbaceous energy plants—such as Miscanthus (Miscanthus sinensis), sida (Sida hermaphrodita Rusby) and cup plant (Silphium perfoliatum L.)—were grown and investigated in the experimental fields of Vytautas Magnus University Agriculture Academy, and the technical means of plant processing and utilization for solid biofuel were investigated. The physical–mechanical properties and quality indicators (moisture content, biometrical properties, density, and resistance to compression) of coarse stem herb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…When evaluating the compressive deformation of pellets, which was the highest in 12.39 ± 0.07% moisture pellets, it reached 2471.5 ± 48.5 N. Unlike in the research of other authors, we can note that the analysis of this corncob index was not found. In studies of pellets from Artemisia dubia by Jasinskas et al [56], when the density of the pellets was 1192.44 kg m −3 and the moisture content was 9.98%, the compressive strength withstood a pressure of 560.36 N. The compressive force of Sida pellets ranged from 557 to 356 N (when the humidity increased from 5% to 15%, the diameter of the pallets was 6.0 ± 0.3 mm) [57]. However, it can be assumed that this indicator was influenced by the size of the pellet under study (the diameter of the pellet ranged from 6.22 to 6.39 mm, and the average pellet length varied from 21.82 to 25.77 mm), since it was produced by a granulator.…”
Section: Discussionmentioning
confidence: 99%
“…When evaluating the compressive deformation of pellets, which was the highest in 12.39 ± 0.07% moisture pellets, it reached 2471.5 ± 48.5 N. Unlike in the research of other authors, we can note that the analysis of this corncob index was not found. In studies of pellets from Artemisia dubia by Jasinskas et al [56], when the density of the pellets was 1192.44 kg m −3 and the moisture content was 9.98%, the compressive strength withstood a pressure of 560.36 N. The compressive force of Sida pellets ranged from 557 to 356 N (when the humidity increased from 5% to 15%, the diameter of the pallets was 6.0 ± 0.3 mm) [57]. However, it can be assumed that this indicator was influenced by the size of the pellet under study (the diameter of the pellet ranged from 6.22 to 6.39 mm, and the average pellet length varied from 21.82 to 25.77 mm), since it was produced by a granulator.…”
Section: Discussionmentioning
confidence: 99%
“…In biomass, this parameter is determined mainly by the type of biomass (chemical composition) [19]. Despite the fact that Festuca rubra is a perennial grass, plants native to Asia and North America are more suitable for energy generation because they are more efficient, bind more CO 2 and contain less ash as a by-product of combustion [20,21]. While the calorific value of Festuca rubra is lower than the plants shown in Table 7, its advantage is the fact that it is relatively resistant to soil contamination with heavy metals.…”
Section: Discussionmentioning
confidence: 99%
“…Energy crops should also be characterized by high nutrient and water use efficiency, as well as a favorable energy balance between energy inputs and outputs. These crops should also be resistant to pests, disease and adverse environmental conditions [21].…”
Section: Introductionmentioning
confidence: 99%
“…[ 39,40 ] On the other hand, direct combustion faces three main disadvantages: reduction of efficiency associated with burning high‐moisture fuels, ash fouling and agglomeration due to alkali compounds found in biomass and the provision of sufficient supplies of bulky biomass. [ 40,41 ]…”
Section: Introductionmentioning
confidence: 99%